Field Evaluation of a Combination of Monospecific Enzyme-Linked Immunosorbent Assays for Type-Specific Diagnosis of Human Immunodeficiency Virus Type 1 (HIV-1) and HIV-2 Infections in HIV-Seropositive Persons in Abidjan, Ivory Coast - Nkengasong, John N. (American Society for Microbiology, 1998)
Serologic distinction between human immunodeficiency virus type 1 (HIV-1) and HIV-2 infection is made difficult because of the cross-reactivity and high cost of existing differentiation assays. An evaluation of a strategy based on a combination of monospecific enzyme-linked immunosorbent assays (ELISAs) (CME), was carried out in Abidjan, Ivory Coast, where both HIV-1 and HIV-2 are present, to determine its accuracy and cost-effectiveness. A total of 1,608 (428 HIV-1-positive, 361 HIV-2-positive, 371 dually HIV-1 and HIV-2 [HIV-D] reactive, and 448 HIV-negative) sera that had been serotyped by a line immunoassay (Peptilav) were tested retrospectively by an HIV-1-monospecific (Wellcozyme HIV Recombinant ELISA) and an HIV-2-monospecific (ICE*-HIV-2) assay. The CME strategy gave concordant results for all of the 428 sera scored as HIV-1 by Peptilav. Of the 361 sera scored as HIV-2 by Peptilav, 316 (87.5%) were scored as HIV-2 by CME; the remaining 45 sera were positive by both monospecific ELISAs (mean optical density ratios, 1.36 for Wellcozyme and 11.30 for ICE*-HIV-2) and were classified as HIV-D by CME. Of the 371 sera classified as HIV-D by Peptilav, 344 (92.7%), 21, and 6 were scored as HIV-D, HIV-1, and HIV-2, respectively, by CME. Additional testing of the discrepant samples by two HIV differentiation assays (RIBA and INNO-LIA) gave results that agreed with those by CME for most of the sera. In addition, 267 other sera were tested prospectively by both CME and Peptilav. In the prospective evaluation, CME results agreed with those by Peptilav for all 106 HIV-1 sera and 40 of the 41 HIV-2 sera. However, of the 120 sera scored as HIV-D by Peptilav, 69 (57.5%), 47 (39.2%), and 4 (3.3%) were scored as HIV-D, HIV-1 only, and HIV-2 only, respectively, by CME. All 47 samples scored as HIV-1 by CME and two of four HIV-2 sera gave concordant results by RIBA, whereas 29 of 47 sera scored as HIV-1 by CME and all four HIV-2 sera gave concordant results by INNO-LIA. The reagent cost for the CME strategy was 59% lower than the cost of the Peptilav strategy. These results suggest that a combination of highly sensitive and specific commercially available monospecific ELISAs is a reliable and cost-effective strategy for type-specific serodiagnosis of HIV-1 and HIV-2 infections in HIV-seropositive persons and therefore represents a recommended strategy in areas where both HIV-1 and HIV-2 are endemic.